Experimental study and numerical simulation on a new type of viscoelastic damper with strong nonlinear characteristics. Issue 4 (21st June 2016) - Gong, Shunming; Zhou, Ying
Summary: In this study, a new type of viscoelastic (VE) damper with strong nonlinear characteristics, showing both softening and hardening, is investigated. Firstly, its performance tests are executed, and its mechanical properties summarized. Then, a shaking table test on a three‐story viscoelastically damped structure is designed to investigate the dissipation characteristics and control effect of this type of VE damper. Six VE dampers were installed in pairs at each story and connected vertically to the upper and lower beams. The structure with additional VE dampers and that without additional VE dampers was subjected to three ground motions whose peak ground accelerations varied from 0.1 to 0.6 g. The experimental results indicate that the control effect on the displacements was remarkable, while the effect on accelerations and shear forces was limited, due to the damper's additional stiffness. With the increment of the damper deformation, the additional stiffness decreased, while the additional effective damping ratio increased at first and then declined. Finally, a simplified analytical method is proposed and applied to simulate the shaking table test using OpenSees. The simulating results validate the analytical method of this type of VE damper. Copyright © 2016 John Wiley & Sons, Ltd.